The social psychologists : research adventures / [Edited by] Gary G Brannigan; Matthew R Merrens - Brannigan, Gary G.edited
This text is designed to provide readers with in-depth first person accounts of research in the area of social psychology. It covers a broad range of topics parallelling those found in most psychology textbooks and shows how different researchers approach significant problems.